Functional changes of the prefrontal cortex, insula, caudate and associated cognitive impairment (chemobrain) in NSCLC patients receiving different chemotherapy regimen - Liu, Siwen; Ni, Jie; Yan, Fei; Yin, Na; Li, Xiaoyou; Ma, Rong; Wu, Jianzhong; Zhou, Guoren; Feng, Jifeng (Frontiers in Oncology, 2022)
Introduction: Chemotherapy-induced cognitive impairment (CICI), termed "chemobrain", is highly prevalent in cancer patients following the administration of chemotherapeutic agents. However, the potential pathophysiological mechanisms underlying CICI remain unknown. This study aimed to explore the functional changes of the brain and associated cognitive impairment in non-small cell lung cancer (NSCLC) patients receiving different chemotherapy regimen. Methods: A total of 49 NSCLC patients (25 patients receiving pemetrexed plus carboplatin chemotherapy (PeCC) and 24 patients receiving paclitaxel plus carboplatin chemotherapy (PaCC)) and 61 healthy controls (HCs) were recruited and underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning, as well as cognitive function tests including Mini Mental State Exam (MMSE), Montreal Cognitive Assessment (MoCA), Functional Assessment of Cancer Therapy-Cognitive Function (FACT-Cog). Brain functional activities were measured by regional homogeneity (ReHo) values, which were calculated and compared between groups. In addition, the associations between ReHo values of changed brain regions and scores of cognitive scales were evaluated. Results: NSCLC patients showed decreased scores of MMSE, MoCA and FACT-Cog and decreased ReHo values in the bilateral superior frontal gyrus (medial), middle frontal gyrus, left inferior frontal gyrus (orbital part) and increased ReHo values in the bilateral insula and caudate. Compared with HCs, patients receiving PeCC demonstrated decreased ReHo values in the right superior frontal gyrus (dorsolateral), left superior frontal gyrus (medial orbital), middle frontal gyrus, insula and rectus gyrus while patients receiving PaCC presented increased ReHo values in the right rolandic operculum, left insula and right caudate. Compared with patients receiving PaCC, patients receiving PeCC had decreased ReHo values in the left superior frontal gyrus (orbital part), middle frontal gyrus and increased ReHo values in the left inferior temporal gyrus, lingual gyrus. Moreover, positive relationships were found between ReHo values of the left and right superior frontal gyrus (medial) and the total scores of FACT-Cog in the patient group. Conclusion: The findings provided evidences that carboplatin-based chemotherapy could cause CICI accompanied by functional changes in the prefrontal cortex, insula, caudate. These might be the pathophysiological basis for CICI of NSCLC patients and were affected by the differences of chemotherapeutic agent administration through different biological mechanisms.